Preparation and Properties of Main Chain Phosphorus Containing Poly(trimethylene terephthalate) Block Copolymers - Cai, Xueming; Lv, Shufang; Jia, Panjin; Han, Qing; Run, Mingtao (Asian Journal of Chemistry, 2015)
A series of phosphorus-containing poly(trimethylene terephthalate) multiblock copolymers were synthesized and characterized on their chemical structure, average molecular weight, thermal stability and flame retardancy. The dihydroxypropyl pentaerythritol phosphate was prepared by using 1,3-propanediol and dichloro phosphorspirol. The phosphorus-containing copolymers were prepared by transesterification and melt-polycondensation method. The results suggest that the block copolyesters were successfully prepared and it shows the characteristics of the intumescent flame retardancy. With increasing phosphorus content in main-chains, the block copolyesters show reduced initial degradation temperatures but increased char residue and gradually increased limiting oxygen index. The dichloro phosphorspirol component contributes flame retardancy in the copolyesters.